Kritik Islam Terhadap Sains Barat - Risal Qori Amarullah; Supriyatin (Edusifa: Jurnal Pendidikan Islam, 2024)
Today, Western civilization, which is based on secularism and materialism, has brought the world to the brink of collapse. The theory of science that is developing at this time shows that there has been a divorce between science and religion. With various scientific discoveries and the spirit of modern progress, religion in the West is no longer related to science. In this study, the author will review Islamic criticism of western science according to Hossein Nasr and Naquib Al-Attas. In writing this journal, the authors used the method of library research, then analyzed it using the method of content analysis, namely, descriptive-analytical analysis, by collecting data from literature related to the discussion of Islamic criticism of western science, according to Hossein Nasr and Naqib Al-Attas. In the results of this study, Nasr argued that his criticism of modernity was first carried out by exploring or tracing the history of Western science. Western science is the main component that supports the growth of modernity. In fact, Western science has lost its transcendental reference due to the separation between science and theology, or religion. Meanwhile, Al-Attas said that the problem of modern science is a problem resulting from secularization. Religion and all metaphysical aspects that govern human reason and language have been eradicated by secularization.Al-Attas emphasized that, in essence, secularism is a statement from a worldview that is un-Islamic, even contrary to Islamic teachings. Therefore, Islam completely rejects any application of the concept of secularism. Only with true faith and knowledge will the Muslims be able to build a glorious Islamic civilization, as demonstrated at the time of the Prophet Muhammad SAW and the great scholars of the past.